Response of Gibberellic Acid Application on Berry Quality of Seeded and Seedless Grapevine Cultivars - Acharya, Anil Kumar; Gautam, Durga Mani; Khatri, Bhim Bahadur; Dahal, Kishor Chandra (Nepalese Horticulture, 2025)
In Nepal, cultivation of grapes in commercial scale has been started since 2016 AD. By the use of chemical flowering inducer, it has become possible to prepone grape production to escape rainy season. However, berry yield and quality are still poor that limit to scale up commercial production in Nepal. Gibberellic Acid (GA3) is commonly used to increase berry yield and quality of grapevines throughout the world. Studies were carried out during 2022-2024 in the Kewalpur Agro-Farm, Dhading, Nepal to optimize the concentration and time of GA3 application to improve the berry quality of different cultivars of grapevine. The experiment included table grape cv. Poloskei Muskotaly (few-seeded) received 0, 5, 10 and 20 ppm; while seedless table grape cv. Talizman (seedless) received 0, 10, 20 and 40 ppm GA₃ at post-flowering, 4–5 mm berry size, and both at post-flowering and 4–5 mm berry size stages. The effect of GA3 varied on berry quality attributes with respect to the cultivars. Application of GA3 significantly increased the quality of berries of seedless (Talizman) and few-seeded (Poloskei Muskotaly) table grapes. GA3 applied at 10 ppm had the highest total soluble solid (TSS) in Talizman, whereas the application of 20 ppm GA3 in Poloskei Muskotaly had the highest TSS, TSS/TTA ratio. Thus, the response of GA3 application on quality attributes varies with respect to the cultivars of grapevine in mid-hill condition of Nepal.